Caring for your health. - Grewer, Eira.; Farrow, Lydia H. (Oxford, New York, Pergamon Press, 1968)
A textbook describing how to build and maintain a healthy body. Includes a chapter on mental health and where and how to obtain health services.
Bibliography: p. 166-167.
Keywords: Health -- Juvenile literature; Health